Challenges and Opportunities in Indonesian Language Education in the Digital Era - Hj St Syahriati (Universitas Syiah Kuala, 2023)
This article discusses challenges and opportunities faced in Indonesian language education in the digital era. The digital era has changed the landscape of education and encourages the use of technology in learning Indonesian. Challenge main encounter is integration appropriate technology in the curriculum and methods appropriate teaching. In addition, adequate access to infrastructure technology and training for teachers to use technology effectively is required. Besides challenges, the digital era also brings significant opportunities. Use of digital media and tools learning interactive can improve involvement of students, facilitating personalized learning, and expanding access to sources of Power education. In addition, digital platforms can also facilitate collaboration between students, teachers and community, producing more connected and based learning projects. In the face of challenges and exploiting this opportunity, it is necessary to collaborate from all stakeholders, including teachers, students, schools, and government, to ensure relevant, empowered Indonesian language education competitively, and in accordance with the demands of the digital era.